Literacy teaching in disadvantaged South African schools. (10th March 2019) - Chetty, Rajendra
Abstract: This article analyses the experiences of teachers of literacy working in underprivileged communities in the Western Cape, South Africa. The purpose is to provide teachers in poorly resourced schools within economically deprived areas an opportunity to voice their experiences of teaching literacy. The article is based on an empirical study using interviews and classroom observation with a sample of 10 teachers. A descriptive account of the observation data was followed by an interpretive analysis. The content analysis of the interview data led to the development of themes and patterns for the discussion. The study reveals the social complexity of literacy education in a post‐apartheid and multilingual society and focuses on teachers in Grade 4 classrooms, which is the grade when learners switch from mother tongue (mainly isiXhosa and Afrikaans) to English as language of instruction. Key factors for literacy underachievement include lack of resources, parental support, lack of teacher knowledge, changes in the curriculum, absence of cognitive activities and the social complexity of poverty. The article recommends that a new model of literacy that challenges inequality and provides strategic and sustained teacher support in disadvantaged schools is crucial in a society emerging from oppression and racism.